Robust industrial Saccharomyces cerevisiae strains for very high gravity bio-ethanol fermentations - Pereira, Francisco B. (2011)
The application and physiological background of two industrial Saccharomyces cerevisiae strains, isolated from harsh industrial environments, were studied in Very High Gravity (VHG) bio-ethanol fermentations. VHG laboratory fermentations, mimicking industrially relevant conditions, were performed with PE-2 and CA1185 industrial strains and the CEN.PK113-7D laboratory strain. The industrial isolates produced remarkable high ethanol titres (>19%, v/v) and accumulated an increased content of sterols (2 to 5-fold), glycogen (2 to 4-fold) and trehalose (1.1-fold), relatively to laboratory strain. For laboratory and industrial strains, a sharp decrease in the viability and trehalose concentration was observed above 90 g l-1 and 140 g l-1 ethanol, respectively. PE-2 and CA1185 industrial strains presented important physiological differences relatively to CEN.PK113-7D strain and showed to be more prepared to cope with VHG stresses. The identification of a critical ethanol concentration above which viability and trehalose concentration decrease significantly is of great importance to guide VHG process engineering strategies. This study contributes to the improvement of VHG processes by identifying yeast isolates and gathering yeast physiological information during the intensified fermentation process, which, besides elucidating important differences between these industrial and laboratory strains, can drive further process optimization.